Secagem por atomização de suco de beterraba (Beta vulgaris L.) utilizando diferentes condições operacionais - Carmo, Eloá Lourenço do (2017)
Betalains are compounds, most commonly extracted from beets, that are used in the food industry as natural colorants, in addition to having antioxidant properties. Spray-drying may enhance their stability and the quality of the final powder product, obtained at the end of the process, depends on the operational parameters. Beet powder extract, obtained by spray-drying with maltodextrin (MD), inulin (IN) and whey protein isolate (IPS) as carrying agents, either isolated or combined (MD:IN, MD:IPS, and IN:IPS), was assessed as to its physicochemical and morphologic properties, as well as stability. In general, the treatment with IN:IPS had satisfactory results, which represents innovati on opportunities for the food industry. In this study, we also analyzed the characteristics of particles obtained by spray-drying beet juice at different temperatures (130, 150 and 170ºC) and inulin:whey protein isolate (IN:IPS) ratios at 1:2, 1:1 and 2:1. The overall results showed that the temperature at 170ºC and the ratio at 1:2 were ideal to obtain beet juice powder extract with good physicochemical properties, fit for application onto dietary products. Furthermore, using inulin and IPS as carrying agents draws great attention, due to their potential to aggregate functional properties, since inulin is regarded as prebiotic and whey protein isolate is considered rich in proteins, helping reduce fat contents and maintaining muscle mass in the human body.